The characteristics of SARS‐CoV‐2‐positive children who presented to Australian hospitals during 2020: a PREDICT network study. Issue 5 (13th August 2021) - Ibrahim, Laila F; Tham, Doris; Chong, Vimuthi; Corden, Mark; Craig, Simon; Buntine, Paul; Jani, Shefali; Zhang, Michael; George, Shane; Kochar, Amit; O'Brien, Sharon; Robins‐Browne, Karen; et al.
Abstract: Objectives: To examine the epidemiological and clinical characteristics of SARS‐CoV‐2‐positive children in Australia during 2020. Design, setting: Multicentre retrospective study in 16 hospitals of the Paediatric Research in Emergency Departments International Collaborative (PREDICT) network; eleven in Victoria, five in four other Australian states. Participants: Children aged 0‒17 years who presented to hospital‐based COVID‐19 testing clinics, hospital wards, or emergency departments during 1 February ‒ 30 September 2020 and who were positive for SARS‐CoV‐2. Main outcome measures: Epidemiological and clinical characteristics of children positive for SARS‐CoV‐2. Results: A total of 393 SARS‐CoV‐2‐positive children (181 girls, 46%) presented to the participating hospitals (426 presentations, including 131 to emergency departments [31%]), the first on 3 February 2020. Thirty‐three children presented more than once (8%), including two who were transferred to participating tertiary centres (0.5%). The median age of the children was 5.3 years (IQR, 1.9‒12.0 years; range, 10 days to 17.9 years). Hospital admissions followed 51 of 426 presentations (12%; 44 children), including 17 patients who were managed remotely by hospital in the home. Only 16 of the 426 presentations led to hospital medical interventions (4%). Two children (0.5%) were diagnosed with the paediatric inflammatory multisystem syndrome temporally associated with SARS‐CoV‐2 (PIMS‐TS). Conclusion: The clinical course for most SARS‐CoV‐2‐positive children who presented to Australian hospitals was mild, and did not require medical intervention.